Construction readiness parameters for highway projects - A. R., Radzi; Abdul Rahimi, Abdul Rahman; Doh, Shu Ing; M., Esa (2019)
Highways greatly contribute to a country’s economic development and growth. Therefore, it is vital for highway construction projects to complete on time and budget. However, when a project starts construction prematurely, projects frequently experience interruption that eventually resulted in delays, causing a multitude of adverse effects on all project stakeholders. In other words, premature starts are one of the factors of construction delays. However, prior studies have little understanding of information that can help practitioners determine whether a highway project is premature or ready for construction. This study aims to identify the parameters used in practice to differentiate whether a highway construction project is ready or not to begin construction. To achieve this objective, interviews with sixteen industry practitioners working on highway construction projects are being conducted and analyzed. The significant findings include: (1) construction readiness can be assessed even as early as during the project start-up phase; and (2) not fulfilling the construction readiness parameters may cause a work stoppage, inefficient work, rework, and shortages in labor, equipment or materials. This study contributes to the current body of knowledge by identifying the parameters that indicate whether a highway project is construction-ready or construction-not-ready. The lessons from this study could help the industry to avoid premature starts in highway construction projects.